THE EFFECT OF AUDITOR INDEPENDENCE, AUDIT COMPLEXITY, AND TIME BUDGET PRESSURE ON AUDIT QUALITY - Herman Wijaya; Linda Santioso (International Journal of Application on Economics and Business, 2026)
This research aims to investigate how auditor independence, audit task complexity, and deadline pressures affect the quality of auditing work within Public Accounting Firms operating across the Banten area. The methodology adopts a quantitative framework utilizing convenience sampling techniques, gathering primary information via Likert-scale questionnaire instruments. Statistical analysis involves multiple linear regression conducted through SmartPLS 4 software, incorporating responses from 52 audit professionals representing 6 accounting firms. Findings indicate that solely auditor independence demonstrates a meaningful impact on auditing quality, while complexity levels and time constraints fail to show statistically significant effects on audit outcomes.